Android Based Application for Searching Indekos In Pasar Minggu Jakarta South With Location Based Service (LBS) Method - Fauzan, Farhan; Faizah, NM; Koryanto, Lucky (Journal Mobile Technologies (JMS), 2023)
Often the availability of the number of boarding houses is not comparable to the number of boarding house seekers, so boarding seekers must find information more quickly in order to get a place to live according to what they want. Boarding house owners promote their boarding houses in a conventional way, namely by word of mouth, distributing brochures, or posting announcements in public places. Based on these problems, an Android-based boarding house search application is needed, an application system that can be a place for out-of-towners who feel confused in finding boarding houses that suit their wishes, and can help boarding owners promote their boarding houses online via a smartphone based on android. The research objective was to design a boarding house search application in Pasar Minggu, South Jakarta, the method used was the waterfall methodology, which is a system method that begins with the requirements analysis stage, then system design, implementation of application development, and users are carried out. This application system was developed using the Java programming language and utilizing Location Based Services and Google Maps. The results of the research resulted in a boarding house search application that makes it easier for users to find boarding houses according to their needs and also this application can provide information about boarding facilities and this application can also make it easier for boarding house owners to publish their boarding houses.